PEMETAAN KETIMPANGAN FASILITAS PENDIDIKAN DI KABUPATEN PADANG PARIAMAN MENGGUNAKAN K-MEANS CLUSTERING - Mardhatillah, Aulia Nurul; Permana, Dony (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
Differences in educational facilities can influence access to education and the quality of education in a region. The aim of this study is to map the distribution of educational facilities in Padang Pariaman Regency using the K-Means Clustering method. Data were obtained from Badan Pusat Statistik (BPS) which includes the number of schools in each district. The analysis determined the optimal number of Clusters through the Silhouette Score, then Clustered districts based on the characteristics of educational facilities. The results showed that two main Clusters were identified, Cluster 1 comprised the districts with poor educational facilities and Cluster 2 included those with better educational facilities. Comparing this with the school-age population shows several districts having a large number of school-age residents in Cluster 1, implying an uneven distribution of educational facilities. Thus, it calls for policies that would equalize educational facilities more particularly in districts where there is high demand but limited access to those facilities. Among the recommendations is the construction of new schools, the upgrading of existing ones, and access to private institutions to improve access to education. Future research should also consider economic conditions, the number of educators, and the quality of educational facilities to draw more comprehensive policy recommendations.